A Theoretical and Experimental In-Situ Electrochemical Infrared Spectroscopy Study of Adsorbed CO on Pt Dendrimer-Encapsulated Nanoparticles. Issue 4 (4th December 2015) - Anderson, Rachel M.; Zhang, Liang; Wu, Dongjun; Brankovic, Stanko R.; Henkelman, Graeme; Crooks, Richard M.
Abstract : We present a combined experimental and theoretical study of COads on Pt147 dendrimer-encapsulated nanoparticles (DENs). In-situ electrochemical IR spectroscopy reveals an 8 cm −1 redshift of the COads stretching frequency on Pt147 DENs relative to a Pt(111) crystal. This value is in good agreement with the shift calculated by density functional theory. Importantly, the wavenumber shift observed in this study is significantly smaller than has been found previously. We attribute this primarily to the absence of support effects and the narrow size distribution of DENs. The agreement between experiment and theory validates the model nanoparticle system used for the calculations, and this will make it possible to use the COads frequency as a probe to study more complex DEN structures and as a descriptor of the catalytic activity of DENs toward reactions such as formic acid oxidation and methanol oxidation.